Bean rust resistance in the Guatemalan climbing bean germplasm collection. Issue 4 (1st June 2022) - Montejo Domínguez, Luz de María A.; McClean, Phillip E.; Steadman, James; McCoy, Serena; Markell, Samuel; Osorno, Juan M.
Abstract: Common bean ( Phaseolus vulgaris L.) is the main source of protein, fiber, and iron for Guatemala's poorest households. Bean rust (caused by Uromyces appendiculatus (Pers) Unger) can reduce seed yield up to 100%. There is limited information about U. appendiculatus virulence diversity in Guatemala, especially in the mid‐altitude highlands. To address this limitation, in 2015, 23 U. appendiculatus samples were collected in the Western Guatemalan Highlands and characterized as races 63‐1 and 31‐1 using the rust differential set. These two races, along with the newer race 20‐3 found in North Dakota, were used to evaluate the reaction in 372 climbing bean accessions from Guatemala. Most of the accessions were resistant: 82% to race 63‐1, 86% to race 31‐1, and 90% to race 20‐3. Based on a genome‐wide association study (GWAS) using 78, 754 single nucleotide polymorphisms (SNPs), regions on Pv02 (38.13–38.22 Mb) and Pv04 (379 kb) were associated with resistance to race 20‐3; on Pv10 (10.71–10.68 and 11.09 Mb) and Pv04 (1.42 Mb) to race 63‐1; and on Pv04 (39.28 Mb) along with Pv02 (35.92 Mb) to race 31‐1. The regions on Pv04: 379 kb, 1.42 Mb and 39.28 Mb felt close to the genetic block B‐190, containing Ur‐5 and Ur‐14 . Moreover, previously unreported genetic factors for bean rust resistance located on Pv02 (38.13–38.22 Mb), Pv10 (10.71–10.68 Mb), and Pv02 (35.92 Mb) were observed in this population and may prove useful for bean improvement. Using these bean rust‐resistant Guatemalan accessions as parents in a crop improvement program will help to maintain seed yield where the bean rust pathogen is present.